2014
DOI: 10.1017/s0033291714000348
|View full text |Cite
|
Sign up to set email alerts
|

Reduced gray matter volume in the anterior cingulate, orbitofrontal cortex and thalamus as a function of mild depressive symptoms: a voxel-based morphometric analysis

Abstract: Background Studies investigating structural brain abnormalities in depression have typically employed a categorical rather than dimensional approach to depression [i.e. comparing subjects with Diagnostic and Statistical Manual of Mental Disorders (DSM)-defined major depressive disorder (MDD) v. healthy controls]. The National Institute of Mental Health, through their Research Domain Criteria initiative, has encouraged a dimensional approach to the study of psychopathology as opposed to an over-reliance on cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 67 publications
7
78
1
5
Order By: Relevance
“…Therefore, CV reduction in the MDD group, particularly in frontal, medial temporal, and limbic areas, may reflect stress-related neurotoxic effects (Treadway et al 2015) that precede manifestation of illness. This is supported by a recent study that demonstrated an association between ACC and orbitofrontal cortical volumetric reduction and subclinical depressive symptoms in a cohort of non-depressed subjects (Webb et al 2014). Our study extends upon this finding as CV reduction in the VLPFC associated with depressive symptoms along a spectrum from healthy subjects to patients diagnosed with depression.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, CV reduction in the MDD group, particularly in frontal, medial temporal, and limbic areas, may reflect stress-related neurotoxic effects (Treadway et al 2015) that precede manifestation of illness. This is supported by a recent study that demonstrated an association between ACC and orbitofrontal cortical volumetric reduction and subclinical depressive symptoms in a cohort of non-depressed subjects (Webb et al 2014). Our study extends upon this finding as CV reduction in the VLPFC associated with depressive symptoms along a spectrum from healthy subjects to patients diagnosed with depression.…”
Section: Resultssupporting
confidence: 74%
“…Consistent with several structural and functional studies in MDD showing fronto-limbic abnormalities (Etkin, Egner, and Kalisch 2011; Pizzagalli 2011; Heller et al 2013), our study showed that reductions of cortical thickness in the rACC (a limbic area), was associated with symptoms related to emotion dysregulation. This adds to previous work showing that reductions in ACC gray matter is an important neural substrate for affective instability and a potential endophenotype for depression (Boes et al 2008; van Eijndhoven et al 2013; Webb et al 2014). …”
Section: Resultssupporting
confidence: 64%
“…Smaller rACC volumes have been repeatedly linked with elevated depressive symptoms in cross-sectional studies (57, 58). Indeed, within our data, smaller rACC volumes were correlated with higher depression severity at baseline (for HRSD, right rACC r = −.…”
Section: Discussionmentioning
confidence: 99%
“…The primary finding was a relationship between higher severity of depressed mood symptoms and increased left inferior temporal volume. Temporal regions, including the inferior temporal gyrus, have consistently been implicated in structural imaging studies of both major depression and subthreshold depression (Andreescu et al, 2007; Dotson et al, 2009b; Son et al, 2013; Webb et al, 2014). In contrast to reports of reduced temporal volumes related to depression in many studies, there has been a report of increased grey matter volumes in parts of the left temporal lobe associated with depression (Ballmaier et al, 2004).…”
Section: Discussionmentioning
confidence: 99%